Changes of the Education System in Minangkabau Families in the Seribu Rumah Gadang Tourism Area, Sungai Pagu District South Solok Regency - Nofembrid Ekadiani; Nia Pratiwi; Ema Lestari; Riki Hariyanyo; Novrizal Novrizal; Rusdinal Rusdinal; Firman Firman (Budapest International Research and Critics University, 2019)
Education is an effort in shaping the character of students. With the existence of education, a person will have knowledge; have values that are adhered to in accordance with the norms that apply to a culture. Minangkabau is a tribe which contains elements of education, namely the planting of values based on Minangkabau indigenous culture, religious elements, and manners, one of which is in the tourist area of a Seribu Rumah Gadang. Seribu Rumah Gadang area is a traditional tourist area located in Sungai Pagu District, South Solok Regency, West Sumatra Province. There are still many areas where we find these traditional rumah gadang and are well maintained, so this area is dubbed as the most popular traditional settlement. With this nickname, ideally the local people still maintain their traditions well, especially in the pattern of family education. But in reality, juvenile delinquency, courtesy and family manners are a serious problem for the community. The purpose of this study was to analyze how changes in the pattern of education in the Minangkabau family in the tourist area of Seribu Rumah Gadang, Sungai Pagu Subdistrict, South Solok Regency, West Sumatra. This study uses a qualitative approach. The selection of informants using purposive sampling technique. Data analysis techniques are done by reducing data, presenting data, and drawing conclusions. The changes in the pattern of education in the family that occur in the thousand houses of the Gadang are, (1) the reduced interaction between parents and children, (2) the pattern of relationships between uncle and nieces, (3) the community's role in child development.